2011
DOI: 10.1111/j.1742-1241.2011.02643.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of optimal lipid value achievement between 2005 and 2009 in patients with mixed dyslipidaemia on cardiovascular event rates

Abstract: In conclusion, challenges to effective treatment of mixed dyslipidaemia remain, as evidenced by a minority of patients achieving optimal lipid levels. There appears to be an association with incremental lowering of CV event rates beyond LDL-C goal attainment when compared with achieving OLV across the entire lipid panel for LDL-C, TG and HDL-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Patients with DM were less likely to have both LDL-C and non-HDL-C at NCEP goal which is similar to a finding reported from a large US commercial health insurance claims database from 2004 to 2009 and 2007 to 2008 National Health and Nutrition Examination Survey. 12,13 Patients meeting NCEP goals were more likely to be cared for by a cardiologist compared to a primary care physician in the report by Hess et al 11 In contrast to clinical trials where all patients are receiving lipid-lowering drug therapy, we report that in the PINNACLE Registry, about 20% of patients, including more than 10% of those with DM, had no documented lipid-lowering pharmacotherapy despite a documentation of a dyslipidemia and a high frequency of CHD co-morbidities in the patient's medical history. This percentage is similar to the 18% of patients with an LDL-C !130 mg/dl not on lipid-lowering therapy reported in the 2007 to 2008 NAHNES.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients with DM were less likely to have both LDL-C and non-HDL-C at NCEP goal which is similar to a finding reported from a large US commercial health insurance claims database from 2004 to 2009 and 2007 to 2008 National Health and Nutrition Examination Survey. 12,13 Patients meeting NCEP goals were more likely to be cared for by a cardiologist compared to a primary care physician in the report by Hess et al 11 In contrast to clinical trials where all patients are receiving lipid-lowering drug therapy, we report that in the PINNACLE Registry, about 20% of patients, including more than 10% of those with DM, had no documented lipid-lowering pharmacotherapy despite a documentation of a dyslipidemia and a high frequency of CHD co-morbidities in the patient's medical history. This percentage is similar to the 18% of patients with an LDL-C !130 mg/dl not on lipid-lowering therapy reported in the 2007 to 2008 NAHNES.…”
Section: Discussionmentioning
confidence: 98%
“…This contrasts with a frequency of 10.5% reported from 2004 to 2009 US commercial health insurance claims. 13 For this analysis, we were not able to assess the statin dose and thus intensity of therapy. Previous data from PINNACLE indicated that men were more likely than women to be prescribed a statin, and in our larger analysis, men were also more likely to reach NCEP goal lipid levels even after adjustment for statin use.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid disorders can accelerate the atherosclerosis process and its consequences, such as heart failure and coronary atherosclerosis (Ebong et al, 2013;Paramsothy et al, 2010), whereas the control of fasting lipid blood levels leads to a reduction in the cardiovascular risk profile of individuals (Cziraky et al, 2011). Nevertheless, failure to achieve an optimal reduction of lipid levels can often be observed in real life.…”
Section: Introductionmentioning
confidence: 99%